DISREGULATION CHANGES IN THE GLUTAMATERGIC SYSTEM IN CRITICALLY ILL PATIENTS, THE RELATIONSHIP WITH THE MECHANISMS OF TANATOGENESIS - Elena Vladimirovna Alekseeva (Современная наука и инновации)
In the clinical setting was studied as glutamatergic neurotransmitter systems (based on content in the blood plasma glutamic acid and glutamine) in the development of critically ill patients the key mechanisms of tanatogenesis: systemic hypoxia, sepsis, acute renal and liver failure, and acute gastrointestinal failure.